2008
DOI: 10.1590/s0124-00642008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación Inicial del Seguro Popular sobre el Gasto Catastrófico en Salud en México

Abstract: RESUMENObjetivo Estimar el resultado inicial del Seguro Popular de Salud (SPS) sobre el gasto catastrófico en salud (GC) de los hogares. Adicionalmente se estimó la relación de otros factores de importancia sobre el GC. Material y métodos Estudio transversal a partir de la Encuesta de Evaluación del Seguro Popular levantada en los estados de Colima y Campeche en el segundo semestre del año 2002. El estudio se llevó a cabo en el primer semestre del año 2005. Se estimó primero la relación del SPS y otras covaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 5 publications
0
11
1
6
Order By: Relevance
“…While conventional measures of out-of-pocket expenditures find that around 1 or 2 % of households face catastrophic health expenditures (Hernandez-Torres et al 2008;Perticara 2008;SesmaVázquez et al 2005), our results show a much higher percentage of households seriously affected by their medical spending increasing their current poverty level and vulnerability.…”
Section: Discussioncontrasting
confidence: 63%
“…While conventional measures of out-of-pocket expenditures find that around 1 or 2 % of households face catastrophic health expenditures (Hernandez-Torres et al 2008;Perticara 2008;SesmaVázquez et al 2005), our results show a much higher percentage of households seriously affected by their medical spending increasing their current poverty level and vulnerability.…”
Section: Discussioncontrasting
confidence: 63%
“…Likewise, studies have found that households with a lower income level are more vulnerable to catastrophic healthcare spending [17, 18]. Seeking care in a public or private hospital increases the risk of catastrophic health expenditure [19].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the households with most health expenses are those in rural areas, with some household members who are over 60 years old, children or disabled, where the head of household is a woman or a person over 60 years old or a person with little formal education (Sesma et al 2004;Torres and Knaul 2003;Hernández et al 2008). Also, findings show that households with a low economic level are more vulnerable to a drop in income and to incurring in catastrophic out-of-pocket expenditure when faced with a health incident that requires medical attention (Knaul et al 2005;Cruz et al 2006;Hernández et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the Mexican Foundation for Health (Funsalud is the Mexican acronym) put the first catastrophic health spending measurement methodology into operation (Sesma et al 2004). Those studies show that non-insured, poor rural households run the highest risk of catastrophic health spending, as well as households with disabled persons or elderly adults and newborns (Hernández et al 2008;Sesma et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation